2020
DOI: 10.1371/journal.pone.0232765
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenol increases effectiveness of foliar iron fertilization in iron-deficient cucumber

Abstract: The water-soluble fullerenols are novel carbon-based nanomaterials with unique properties, which afford them with wide agricultural applications. Iron (Fe) deficiency is the most common and widespread nutrition disorder affecting plants. Foliar Fe treatments of plants have been carried out with solutions devoid of fullerenol. In this study, the role of fullerenol [C 60 (OH) 22-24 ] in alleviation of Fe deficiency in Cucumis sativus (a Strategy I plant) via foliar fertilization was investigated. Cucumber plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Polyhydroxylated fullerene C 60 (OH) 22–24 was synthesised and identified using previously developed methods, as described recently [ 21 , 36 , 37 ]. The identification of the obtained sample was performed utilising IR spectroscopy, elemental analysis, size distribution, and ζ -potentials study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyhydroxylated fullerene C 60 (OH) 22–24 was synthesised and identified using previously developed methods, as described recently [ 21 , 36 , 37 ]. The identification of the obtained sample was performed utilising IR spectroscopy, elemental analysis, size distribution, and ζ -potentials study.…”
Section: Methodsmentioning
confidence: 99%
“…From the results of elemental analysis, a relative molar weight of 1128 g mol –1 , corresponding to the C 60 (OH) 24 formula, was applied in all further calculations. Size distribution revealed that the hydrodynamic diameters of fullerenol nanoparticles in the binary C 60 (OH) 22–24 –H 2 O system were 21 nm, and ζ -potentials values were −30 mV; therefore, indicating that even at low concentrations ( C = 1 mg L -1 ), fullerenol forms associates in aqueous solution and the solutions are electrokinetically stable [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that the Fe added to the leaves by spraying may have been deposited in the apoplast as inactive Fe. However, recently, the addition of fullerenol to Fe(II)-sulfate sprays has been shown to increase leaf active Fe and successfully suppress Fe deficiency symptoms by increasing the stability of the applied Fe(II) [51]; increasing Fe(II) stability is important for enhancing the potential of foliar Fe fertilization.…”
Section: Fe Activation In Leavesmentioning
confidence: 99%
“…Many studies have also shown that some practices can indirectly promote Fe uptake by plants [19,20]. Conventional tillage (soil plowing at 20 cm) significantly increases Fe accumulation in peanuts by 51.2% compared with that under no tillage [21]. Short, highfrequency irrigation periods alleviate leaf chlorosis in apple and pear trees in calcareous soils with a caliche layer [22].…”
Section: Introductionmentioning
confidence: 99%